Comorbidity in Aging and Dementia: Scales Differ, and the Difference Matters - Borson, Soo; Scanlan, James M.; Lessig, Mary; DeMers, Shaune (The American journal of geriatric psychiatry, 2010)
Accurate assessment of the effect of dementia on healthcare utilization and costs requires separation of the effects of comorbid conditions, often poorly accounted for in existing claims-based studies. To determine whether two different types of comorbidity and risk adjustment scales, the Chronic Disease Score (CDS) and the Cumulative Illness Rating Scale for Geriatrics (CIRS-G), perform similarly in older persons with and without dementia. All subjects in the community-outreach diagnostic program of the University of Washington Alzheimer's Disease Research Center Satellite were included (N = 619). Subjects' mean age was 75 ± 9 years; 40% were cognitively normal, 17% were cognitively impaired but not demented, and 43% were demented. CDS and CIRS-G scores (neuropsychiatric disorders excluded to reduce colinearity with group) were examined across strata of age, education, and cognitive classification by using analysis of variance, analysis of covariance, and linear regression. CIRS-G scores were sensitive to factors known to be associated with chronic disease burden, including age (F = 21.3 [df = 2, 616], p <0.001), education (F = 6.6 [df = 3, 614], p <0.001), and cognitive status (F = 40.5 [df = 2, 616], p <0.001), whereas the CDS was not. In the subset of persons with CDS scores of 0 (40% of the total sample), CIRS-G scores ranged from very low to high burden of disease and remained significantly different across age, education, and cognitive status groups. In regression analyses predicting CIRS-G score, CDS score and cognitive status interacted (β = −0.10, t = 1.9 [df = 1, 609], p = 0.06). After controlling for age, the amount of variance shared by the CIRS-G-13 and CDS differed by cognitive group (>32% for normal and mildly impaired groups combined, 17% for dementia). Different methods of measuring and adjusting for comorbidity are not equivalent, and dementia amplifies the discrepancies. The CDS, if used to control for comorbidity in comparative studies of healthcare utilization and costs for persons with and without dementia, will underestimate burden of comorbid disease and artificially inflate the costs attributed to dementia.